Pengaruh Postal Mails and Parcel Revenue dan Financial Services Revenue Terhadap Net Income PT Pos Indonesia (Persero) - Tira Nurwulansari; Derdjo Djony Saputro (Winter Journal: IMWI Student Research Journal, 2022)
This study aims to determine whether the postal mails and parcel income and financial services income affect net income. The research method uses non-probability sampling techniques with saturated sampling methods. The population and sample in this study are PT Pos Indonesia (Persero) and the period of this study starting from 2008 to 2016. Data analysis method used is using a classic assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, while for hypothesis testing using multiple linear analysis. Result: That the postal mails and income package do not have a significant influence on PT Pos Indonesia (Persero) net income, whereas financial services income has a significant influence on PT Pos Indonesia (Persero) net income, and postal mails and parcel revenue and financial services revenue significantly influence the net income of PT Pos Indonesia (Persero).